THE INFLUENCE OF MACROECONOMICS AND FUNDAMENTAL FACTORS TOWARD BETA STOCK OF FOOD AND BEVERAGE COMPANY LISTED IN INDONESIA STOCK EXCHANGE - Josephine H.L.H Situmorang; Purwanto . (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2020)
This research aims to analyze the influence of macroeconomics and fundamental factors toward beta stock on Indonesia’s food and beverage company listed in the Indonesia Stock Exchange from 2015 to 2019. There are four independent variables such as exchange rate, current ratio, debt to equity ratio, and return on equity are examined by descriptive statistical analysis, classical assumption test, multiple linear regression, and hypotheses testing. This research used quantitative research. Through purposive sampling, this research got 65 observations from 13 companies in 5 years which fulfill the criteria. The population of this research is food and beverage companies listed on Indonesia Stock Exchange. The outcomes reveal a value of adjusted R-squared among dependent variables is 6.41%. The variables of the exchange rate, debt to equity ratio, and return on equity have no partially significant influence on beta stock while the current ratio has a significant partial influence in hypotheses testing. Simultaneously, the exchange rate, current ratio, debt to equity ratio, and return on equity have no significant influence toward the beta stock of food and beverage companies. Before making investment and operational decisions, the investors and companies get the information from the result of this research in analyzing stock risk.